Development of bio-based adhesive using tannery shaving dust: Process optimization using statistical and artificial intelligence techniques - Gebremariam, Ejigayehu Chakiso; Malede, Yohanes Chekol; Prabhu, S. Venkatesa; Varadharajan, Venkatramanan; Manivannan, S.; Jayakumar, Mani; Gurunathan, Baskar (Bioresource technology reports, 2023)
The present work was aimed to develop an optimized process for producing a bio-based adhesive material using tannery chrome shaving dust using statistical and artificial intelligence techniques. The collagen was extracted from the waste dust of tannery shavings using alkali hydrolysis and was used to produce the bio-adhesive. To attain a global optimizing solution, the experimental data were subject to ANN analysis for acquiring the maximized peel strength of bio-based adhesive. The optimal conditions were found to be working temperature 65 °C, concentration of polyvinyl alcohol 3.2 % and concentration of glycerol 4.2 %. The experimental peel strength of 12.5 N/mm was obtained at optimal conditions, thus the predicted conditions fitted well-agreement with ANN the model prediction. The produced bio-adhesive was characterized using FTIR and TGA analyses. In addition, the acquired bio-based adhesive was characterized to be well-comparable with commercially available chemical-based adhesives. [Display omitted] •Bio-adhesive was produced using tannery chrome shaving dust was prepared.•The selected factors on strength of bio-adhesive were optimized using RSM and ANN.•Selected factors such as polyvinyl alcohol, glycerol, and temperature were optimized.•Extracted collagen and bio-adhesive were characterized using FTIR and TGA.